Os desafios da política de educação para jovens e adultos: o analfabetismo e as medidas para ampliação da escolarização no município de Cascavel-PR (2006-2008) - Dolla, Margarete Chimiloski (2009)
In this study we examined how the formation and organization of Youth and Adults (EJA) in Paraná State, from early 1970 until the present, and its offer in Cascavel, in the period 2006 to 2008. We deal, thus the provision of adult education courses in Basic Education - Phase I (1st to 4th grades), the responsibility of the public health system, and elementary - Phase II (5th to 8th grades) and Secondary Education State Center Basic Education for Youths and Adults CEEBJA Teacher Joaquina Mattos Branco, the responsibility of the state public. Let us resume, for both the historical antecedents of adult education in Brazil, from the movements of the "Enthusiasm for Education" and "Teaching Optimism." In this historic return, the 1990s was fundamental for establishing the basis for our analysis, since the EJA had the right formalized into law, a duty of a mandatory bid for the Brazilian from the 1988 Constitution. In the 1990s, so it was possible to verify the commitments to the kind of adult education at the International Conferences, National and State Boards of Education, which were decisive for the elaboration of educational policies that led to programs / projects to meet the literacy framework in Brazil and the state of Paraná contributed to strengthen the implementation of pedagogical presence. We found that over a period of about three decades, the legislation Parana on the provision of adult education has undergone many changes with regard to the form of care (for face semi-distance), the workload and the age required for admission and enrollment in courses for Supplemental Examinations. Regarding the data in the supply of adult education in Cascavel we can say that the indices did not finish the courses and enrollment in Supplemental Examinations were exorbitant demystifying to some extent, the supposed belief that the ticket for adult education, through the Examinations Supplemental is a quick and easy route to obtain certification.